Comparative Study on Safety & E cacy of Glimepiride-Metformin with Vildagliptin-Metformin Combination in Patients with Type-2 Diabetes Mellitus (Ibrahim Cardiac Medical Journal, 2026)
Background & objective: Metformin is a cornerstone in the management of Type 2 Diabetes Mellitus (T2DM); however, monotherapy with metformin often fails to achieve optimal glycemic control in many patients, especially in elderly or inadequately managed cases. Consequently, combination therapies involving agents such as dipeptidyl peptidase-4 (DPP-4) inhibitors (e.g., vildagliptin) or sulfonylureas (e.g., glimepiride) are frequently employed. Nonetheless, limited studies have directly compared the efficacy and safety profiles of commonly used combinations of metformin with vildagliptin (MF-VG) versus metformin with glimepiride (MF-GP). This study aimed to evaluate and compare the efficacy and safety of these two combination therapies in patients with uncontrolled T2DM.Methods: This randomized, comparative clinical trial was conducted over a one-year period (July 2019 to June 2020) at the Department of Pharmacology and Therapeutics, in collaboration with the Rajshahi Diabetic Association, General Hospital, Rajshahi. A total of 70 patients with uncomplicated T2DM, with or without stable co-morbidities, who had been on metformin therapy (1000-2500 mg/day) for at least four weeks but remained inadequately controlled (HbA1c ≥ 6.5%, FBG ≥ 126 mg/dL, or PPG ≥ 200 mg/dL), were enrolled. Participants were randomly assigned to two groups: MF-VG (n = 35) and MF-GP (n = 35). Outcomes—measured at 6 and 12 weeks—included changes in FBG, PPG, HbA1c, and the incidence of adverse events.Results: The two groups were comparable in terms of age, sex, and BMI (p = 0.490, p = 0.811, and p = 0.392, respectively). Baseline glycemic parameters (FBS, PPG, HbA1c) were elevated above the normal range, with no significant differences between groups (p = 0.104, p = 0.108, and p = 0.130, respectively). Both groups demonstrated significant reductions in FBG, PPG, and HbA1c levels from baseline to 12 weeks (p < 0.05). The mean FBS decreased by 2.7 mmol/L in the MF-VG group and 2.6 mmol/L in the MF-GP group. PPG reductions were 4.3 mmol/L and 4.4 mmol/L, respectively. HbA1c levels declined by approximately 1.5% in the MF-VG group and 1.1% in the MF-GP group. Notably, the incidence of weight gain and hypoglycemia was higher in the MF-GP group.Conclusion: Both metformin-vildagliptin and metformin-glimepiride combinations effectively improve glycemic control in patients with uncontrolled T2DM on metformin monotherapy. However, considering safety profiles—particularly the lower incidence of weight gain and hypoglycemia—the MF-VG combination appears to be a more favorable therapeutic option. These findings support the use of vildagliptin in combination with metformin as an effective and safer alternative to glimepiride-metformin therapy in managing uncontrolled T2DM.Ibrahim Card Med J 2024; 14 (2): 10-16